MENTAL PERUBAHAN MENUJU MUTU PENDIDIKAN ISLAM - maskuri ismail; Minhaji Minhaji (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2019)
Education quality studiesare always dynamic, because the quality character always keeps up the times. Society demands for the implementation of Islamic education quality should be responded to well. Preparing and creating an atmosphere of quality culture in educational environment by mental change is the necessity. Efforts to forming the quality of education must begin by education providers. Islamic boarding schools as the one form of Islamic educational institutions, with Kyai as central figures are very important in responding any changes towards quality in education. Mental and quality culture also accompany management in Islamic education. Adequate professionalism and skillsarethe investment of resources which also determines quality of Islamic education. For this reason, the values of Islamic teachings contained in Alqur’an concerning quality, management, and change should be contextual.